2020
DOI: 10.1007/s11219-019-09495-w
|View full text |Cite
|
Sign up to set email alerts
|

Towards a software quality certification of master data-based applications

Abstract: Master data management (MDM) can provide an integrated and unified view of key business entities to offer better support in business processes. Due to the very nature of master data-based applications, it is possible to use data with the highest possible level of quality. MDM can help ensure that some common concerns, like duplicates or inconsistencies, are prevented by sharing a 'single version of the truth' throughout the organisation, and, in some cases, allowing collaborative updates to the master data rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…This investigation is motivated by some organizations' need to evaluate the quality of the master data repositories. Based on our experience in previous data quality evaluations and certification projects (Gualo et al, 2020), and on the inspection of the scarce related literature we found, in this section, we present the master data quality model we tailored to be used with the framework introduced in Section 2.2. The adaptation involves revising the ISO/IEC 25012 data quality model and related ISO/IEC 25024 data quality properties from the point of view of master data and considering its unique features.…”
Section: Tailoring a Quality Model For Master Data Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation is motivated by some organizations' need to evaluate the quality of the master data repositories. Based on our experience in previous data quality evaluations and certification projects (Gualo et al, 2020), and on the inspection of the scarce related literature we found, in this section, we present the master data quality model we tailored to be used with the framework introduced in Section 2.2. The adaptation involves revising the ISO/IEC 25012 data quality model and related ISO/IEC 25024 data quality properties from the point of view of master data and considering its unique features.…”
Section: Tailoring a Quality Model For Master Data Quality Evaluationmentioning
confidence: 99%
“…One advantage is that this repository can be used as an authoritative source of data to reliably and consistently feed business processes in different scenarios by different actors in other contexts (Allen and Cervo, 2015;Haneem et al, 2017Haneem et al, , 2019. Investments in Master Data Management (MDM) allow the minimization of redundant efforts in repeatedly fixing the same data quality concerns through different departments (Allen and Cervo, 2015;Gualo et al, 2020). Consequently, the better the levels of data quality of the master data repositories, the better the intra-and inter-organizational performance.…”
Section: Introductionmentioning
confidence: 99%
“…Fernando Gualo [3] et al assessed the "Functional Suitability" of MDM applications by considering useful necessities from section 100 to 140 of ISO 8000 and proposed a solution by considering the appraisal and affirmation of Functional Suitability of MDM applications. In addition to basic requirements, test cases are also designed required for the evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Master data deals with the critical data entities of a company such as clients, items and resources that are shared across value-based applications. It additionally enables the development of a 'single version of truth' [3]. The technical operations assisted by MDM activities include Data quality improvement, Master Data creation and Data engineering [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Heck et al (2010) and Yahya (2007) focused on the product approach. Similarly, Gualo et al (2020) worked towards certification of the functional suitability for master data management applications. Nevertheless, the quality of newly developed software cannot be immediately determined by using the product approach because the software needs to be used for a period of time before the quality can be determined (Baharom et al, 2011;Heck et al, 2010).…”
Section: Introductionmentioning
confidence: 99%